CYBERSPACE, THE SOCIAL GRAPH AND NEW MEDIA RUPTURE- TALK - Stevenson, Michael (AoIR Selected Papers of Internet Research, 2014)
From visions of virtual community in the early 1990s to more recent claims that social media are instilling a culture of openness, the web has long been associated with radical change in the media landscape. What should be made of these narratives of rupture in new media culture? This paper explores what new media rupture-talk is and what it does, taking the concepts of cyberspace and the social graph as its central examples.